2020
DOI: 10.1016/j.hrthm.2019.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new ultralow-dose radiation protocol for electrophysiological device implantation: A near-zero fluoroscopy approach for device implantation

Abstract: BACKGROUND Radiation is one of the main hazards of electrophysiological device implantation, and insertion of cardiac resynchronization therapy (CRT) devices in particular is associated with high radiation doses. OBJECTIVE The purpose of this study was to evaluate the impact of a new ultralow-dose radiation protocol on radiation doses, success rate, and safety of electrophysiological device implantations. METHODS In 2018, we established a new ultralow-dose radiation protocol (reduced pulse width, increased thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…This resulted in a median dose of 30 CGycm 2 for single chamber devices and 326 CGycm 2 for CRT devices. (195) By comparison, the doses in the present study are reported as 22 and 410 CGycm 2 , which appear to be similar. A further study in 2019 established a multicentre DRL for device implants.…”
Section: Current Implicationssupporting
confidence: 69%
“…This resulted in a median dose of 30 CGycm 2 for single chamber devices and 326 CGycm 2 for CRT devices. (195) By comparison, the doses in the present study are reported as 22 and 410 CGycm 2 , which appear to be similar. A further study in 2019 established a multicentre DRL for device implants.…”
Section: Current Implicationssupporting
confidence: 69%
“…Many EP labs have upgraded their x-ray equipment to program lower frame or pulse rates. In the most aggressive attempt to overhaul all methods to minimize patient and physician exposure, an ultralow-dose radiation protocol was adopted in one German hospital for all pacemaker and defibrillator implants [ 28 ]. Through the combined use of reduced pulse width and rate of emission, increased thickness of copper filters, reduced detector entrance dose, and an optimization of postprocessing image settings, the physicians were able to reduce the effective dose exposure by 59%.…”
Section: The Rise and Fall Of Ep Fluoroscopymentioning
confidence: 99%
“…Furthermore, the fluoroscopic equipment must necessarily remain in operation throughout the catheter placement procedure providing real-time feedback to the medical operator. This, of course, conflicts with the need to reduce the radiation dose absorbed both by the patient and even more so by the medical operator [ 8 , 9 ]. To try to reduce quantum noise while maintaining a low radiation dose, various image processing techniques have been proposed, and some of these are implemented by modern fluoroscopic systems.…”
Section: Introductionmentioning
confidence: 99%